Frequency and Factors Leading to Non-Adherence to SGLT-2 Inhibitors in Patients with Ischemic Heart Disease - Saleem, Atta ur Rehman URF Saleem; Khan, Navedullah; Buriro, Gulzar Ali; Kumar, Mukesh; Amin Ullah; Jibran ul Haq; Hassan Ali, Hassan Ali (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the frequency of non-adherence to sodium-glucose cotransporter-2 (SGLT-2) inhibitors in patients with ischemic heart disease (IHD) and identify factors contributing to non-adherence at National Institute of Cardiovascular Diseases Karachi, Pakistan. Methodology: A prospective descriptive study was conducted on 171 IHD patients prescribed SGLT-2 inhibitors at the National Institute of Cardiovascular Diseases, Karachi. Adherence was assessed using the MMAS-8© scoring system, categorizing patients into high adherence (score = 8), medium adherence (score 6–7), and low-adherence (score < 6), we will take a score of <6 as Non-adherence. Factors influencing adherence, including patient education about SGLT2 inhibitors, side effects, and cost, were analyzed. Statistical analysis was performed using chi-square tests with a significance level of P ≤ 0.05. Results: Among 171 patients, 58 (33.91%) demonstrated high adherence, 42 (24.56%) had medium adherence, and 71 (41.53%) were non-adherent (P = 0.003). The primary factors influencing non-adherence included lack of patient education (24 patients, 14.03%, P = 0.001), side effects (19 patients, 11.11%, P = 0.001), and cost barriers (15 patients, 8.77%, P = 0.001). Dizziness was the most frequently reported side effect (12 patients, 63.16%). Conclusion: The study highlights significant non-adherence to SGLT-2 inhibitors, driven by education gaps, side effects, and cost issues. Addressing these factors through patient education about SGLT2 inhibitors, affordable access programs, and proactive side effect management can enhance adherence and improve cardiovascular outcomes in IHD patients.